2023
DOI: 10.1161/strokeaha.123.044113
|View full text |Cite
|
Sign up to set email alerts
|

Study of Rivaroxaban for Cerebral Venous Thrombosis: A Randomized Controlled Feasibility Trial Comparing Anticoagulation With Rivaroxaban to Standard-of-Care in Symptomatic Cerebral Venous Thrombosis

Abstract: Background: Emerging data suggest that direct oral anticoagulants may be a suitable choice for anticoagulation for cerebral venous thrombosis (CVT). However, conducting high-quality trials in CVT is challenging as it is a rare disease with low rates of adverse outcomes such as major bleeding and functional dependence. To facilitate the design of future CVT trials, SECRET (Study of Rivaroxaban for Cerebral Venous Thrombosis) assessed (1) the feasibility of recruitment, (2) the safety of rivaroxaban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 34 publications
1
25
0
1
Order By: Relevance
“…Conversely, most recent data from the SECRET Trial (2023) [33], a phase 2 feasibility trial comparing rivaroxaban to standard-of-care (VKAs) in symptomatic CVT, reported numerically more bleeding events at 180 days in patients taking rivaroxaban, although rates of bleeding events and recurrent VTE were low overall and in keeping with previous evidence [33].…”
Section: Treatment and Prognosissupporting
confidence: 57%
See 1 more Smart Citation
“…Conversely, most recent data from the SECRET Trial (2023) [33], a phase 2 feasibility trial comparing rivaroxaban to standard-of-care (VKAs) in symptomatic CVT, reported numerically more bleeding events at 180 days in patients taking rivaroxaban, although rates of bleeding events and recurrent VTE were low overall and in keeping with previous evidence [33].…”
Section: Treatment and Prognosissupporting
confidence: 57%
“…Im Gegensatz dazu berichteten die neuesten Daten aus der SECRET-Studie (2023) [33], einer Phase-II-Machbarkeitsstudie, in der Rivaroxaban mit Standardtherapien (VKAs) bei symptomatischen CVT verglichen wurde, nach 180 Tagen von erhöhten Blutungen bei Patienten, die Rivaroxaban einnahmen. Und dies, obwohl die Raten der Blutungsereignisse und rezidiven VTE insgesamt niedrig waren und früheren Erkenntnissen entsprachen [33].…”
Section: Behandlung Und Prognoseunclassified
“…[22][23][24] A prospective cohort from a Canadian randomized trial found that although 72% of individuals with CVT remained functionally independent at the time of their presentation, there was an overall substantial burden of headache, fatigue, low mood, and impaired cognitive performance. 25 A retrospective study from China including 303 patients with CVT who were employed or students before their index event found that 42% had not returned to work or school at 6 months, despite 87% reaching functional independence at the time of assessment. 26 Epilepsy may affect >10% of individuals with CVT, with risk factors including seizures at the time of onset, decreased level of consciousness or focal deficits, Prevalence of sinus involvement in CVT.…”
Section: Long-term Symptoms and Cvt Recurrencementioning
confidence: 99%
“…SECRET (Study of Rivaroxaban in Cerebral Venous Thrombosis) was a phase II trial that randomized 53 participants with CVT 1:1 to rivaroxaban 20 mg daily versus standard-of-care anticoagulation (warfarin; target international normalized ratio, 2.0-3.0] or LMWH) for a minimum of 6 months. 25 There was no requirement for lead-in parenteral anticoagulation. The trial excluded individuals with pregnancy and antiphospholipid antibody syndrome.…”
Section: Re-spect Cvt (A Clinical Trial Comparing Efficacy and Safety...mentioning
confidence: 99%
“…However, the efficacy and safety of DOACs in patients with CVT remains unclear. Considering these, recent randomized clinical trials (RCTs) such as RE-SPECT CVT (Safety and Efficacy of Dabigatran Etexilate Versus Dose-Adjusted Warfarin in Patients With CVT) 16 and SECRET (Study of Rivaroxaban for Cerebral Venous Thrombosis) 17 have examined the use of DOACs compared with standard of care in patients with CVT. Therefore, we performed a systematic review and meta-analysis of clinical trials to evaluate the efficacy and safety outcomes of DOACs when compared with the current standard of care in adult patients with CVT.…”
Section: Introductionmentioning
confidence: 99%